Innovative Design and Analysis of the Maglev Cam Mechanism - Zhao Peng; Yang Guilin; Liu Shulin; Tat Joo Teo Daniel; Chen Jinhua; Zhang Jie (Jixie chuandong)
In order to achieve high- speed,low- impact,frictionless and high- precision motion of the cam mechanism,an innovative design of a magnetically levitated cam mechanism is proposed. Based on electro- magnetic theory,a theoretical formula for computing the levitation force is deduced,which facilitates the adaptive motion control of the maglev cam system. In order to figure out the optimum design parameters to maximize the levitation force,the computer simulation is conducted by using ANSYS. The optimization design analysis and structure design of the proposed maglev cam mechanism are carried out,a basis for the future experimental study is provided.